2013
DOI: 10.1182/blood-2012-05-431486
|View full text |Cite
|
Sign up to set email alerts
|

Secondary genetic lesions in acute myeloid leukemia with inv(16) or t(16;16): a study of the German-Austrian AML Study Group (AMLSG)

Abstract: • More than 90% of the patients with inv (16)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
150
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(173 citation statements)
references
References 45 publications
16
150
2
5
Order By: Relevance
“…Some studies suggested that KIT or multiple mutations may confer adverse prognosis in CBF AML [40,70]. This has not been our experience with the FLAG-Ida/GO, where the efficacy of the regimen may have overcome the adverse impact of the mutations.…”
Section: Core Binding Factor Amlmentioning
confidence: 92%
“…Some studies suggested that KIT or multiple mutations may confer adverse prognosis in CBF AML [40,70]. This has not been our experience with the FLAG-Ida/GO, where the efficacy of the regimen may have overcome the adverse impact of the mutations.…”
Section: Core Binding Factor Amlmentioning
confidence: 92%
“…9 A mutation of KIT gene is found in 15%-35% of CBF-AML, KIT mutations being more frequent in inv(16)/t(16;16) than in t(8;21). 7 KIT mutations have been shown to co-operate with CBF oncogenic event to induce leukemia in vitro and in mouse models. These mutations result in the activation of many intracellular pathways, including JAK/STAT, PI3-kinase/Akt and ERK/MAP-kinase, promoting cell growth and differentiation, but also proliferation and apoptosis inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Among them, KIT and FLT3 gene mutations have been associated with a higher risk of relapse in many retrospective studies. In the CBF-2006 study (EudraCT n. 2006-005163-26; clinicaltrials.gov identifier: 00428558), the French AML Intergroup prospectively assessed the respective prognostic values of RTK mutations and MRD in CBF-AML patients in a therapeutic program consisting in three consecutive high-dose AraC courses (HiDAC) as consolidation program after achievement of complete remission (CR) by anthracycline and standard dose cytarabine induction sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in KIT and RAS were less likely to occur concurrently, whereas mutations in KIT and FLT3 occurred concurrently in 6% of patients. 73 Of these secondary genetic lesions, KIT mutation and trisomy 22 were significant independent factors predictive of RFS in multivariable analysis; FLT3 mutations, trisomy 22, and trisomy 8 were significant independent predictors for OS. Despite emerging data on the prognostic relevance of mutations in the IDH and DNMT3A genes (see earlier discussions), the role of these molecular lesions on the risk stratification of patients with AML has yet to be defined.…”
Section: Molecular Markers and Risk Stratificationmentioning
confidence: 99%
“…27,33,35,72 In a recent analysis from the German-Austrian AML Study Group, the frequency and prognostic impact of secondary genetic lesions were evaluated in patients with CBF AML who were treated in prospective trials (n=176). 73 Secondary chromosomal abnormalities were found in 39% of patients, with the most common abnormalities being trisomy 22 (18%), trisomy 8 (16%), and 7q deletion (5%). Secondary genetic lesions were found in 84% of patients, including mutations in RAS (53%; NRAS in 45%; KRAS in 13%), KIT (37%), and FLT3 (17%; FLT3-TKD in 14%; FLT3-ITD in 5%; both mutations present in 2%).…”
Section: Molecular Markers and Risk Stratificationmentioning
confidence: 99%